Making a Simple Prism as an Alternative Physics Practicum Tools - Via Monica Devi; Aris Doyan; Kosim Kosim (AMPLITUDO : Journal of Science and Technology Innovation, 2023)
Refraction of light occurs due to the difference in the speed of light in the two mediums where the speed of light in a dense medium is smaller than the speed of light in a less dense medium. One of the refraction phenomena also occurs in prism glass. Prisms help scatter incoming light from monochromatic light sources. To prove this, refraction experiments can be carried out using a prism. Where the prism used is made manually using used glass made of acrylic. The prism that is made is then filled with water on the inside and a test is carried out to determine the refraction and the value of the angle of deviation. Based on the results obtained, the refraction of the prism glass made in where a beam of light that passes through the prism is deflected from its original direction, while the angle of deviation of the rays is proportional to the angle of incidence